Children and HIV/AIDS: from research to policy and action in resource-limited settings. - (:unkn) unknown (My University, 2008)
During the past two decades, international efforts to fight against HIV/AIDS have yielded important research successes for child survival in developing countries. Lessons have been learned about which prevention and care approaches are most efficient in responding to the needs of children affected by HIV/AIDS. However the transition from research to action remains largely insufficient. Without the universal access of currently available PMTCT interventions, one out of three infants born to HIV-infected mothers will continue to contract HIV and most of them will die within their first year of life. Yet, economical and cultural barriers limit severely the coverage, acceptability and use of PMTCT services. There is also enough evidence today to roll out paediatric HIV care and treatment, at least at the same speed and extent than adult care and in priority with a family-targeted approach. This however requires improving health care systems as well as long-term political commitment and funding at international, national and more local levels, which is far from guaranteed. Current knowledge indicates that orphans and vulnerable children pay a large tribute to HIV/AIDS and deserve a large-scale response, as their needs remain grossly under-met. Finally, and in line with a growing international consensus, it is more than ever obvious that the fight against HIV/AIDS requires the scaling-up and intensification of primary HIV prevention, as part of a comprehensive response that simultaneously expands access to treatment and care.
Keywords: African Research